Road Environment as Predictor of Road Traffic Accidents Involving Heavy-Duty Automobiles in Northeast Nigeria - Kumazhege, Stephen Z.; Ibrahim, Umar Aliyu (Darul Yasin Al Sys, 2024)
This study examined road environment as a predictor of road traffic accidents involving heavy-duty automobiles in northeast Nigeria. Survey research was adopted for the study through a structured questionnaire. 235 FRSC, Traffic Police, VIOs and Drivers were sampled for the study. Regression analysis was used to test the hypothesis with the help of SPSS v.25 software. The results indicated that road signs system, natural road environment, and road conditions significantly influence road traffic accidents involving heavy-duty automobiles in Northeast Nigeria. Consequently, it was recommended that the Federal Government should provide an adequate and functional road signs system on Northeast Nigeria highways.